Long-term exposure to TET increases body weight of juvenile zebrafish as indicated in host metabolism and gut microbiome. (June 2020) - Keerthisinghe, Tharushi Prabha; Wang, Feng; Wang, Mengjing; Yang, Qin; Li, Jiawei; Yang, Jingfeng; Xi, Lin; Dong, Wu; Fang, Mingliang
Graphical abstract: Highlights: The body weight of juvenile zebrafish was increased upon tetracycline (TET) exposure. Lipid vacuoles were generated in the zebrafish livers after TET exposure. Hepatic triglyceride (TAG) levels were upregulated after TET exposure. Hepatic metabolism was altered upon TET exposure. Zebrafish gut microbial community diversity was increased after TET exposure. Abstract: The application of tetracycline (TET) is very common in medical treatment, fisheries, and animal husbandry, resulting in its frequent detection with abundant concentrations in the aquatic environment. Though the effects of TET on zebrafish ( Danio rerio ) at embryonic and larval stages have been reported, there is very limited information on the possible long-term effect on aquatic fishes at the juvenile stage, especially at environmentally relevant levels. In this study, we have exposed juvenile zebrafish to two levels of TET at 1 and 100 µg/L for one month until their adulthood. The result showed that both levels of TET can significantly increase the body weight of the zebrafish, while there is no change in the body length. TET exposure also affected the liver microstructure by lipid vacuoles generation and global lipidomics analysis revealed a significant upregulation in hepatic triglyceride (TAG) levels. The metabolomics analysis showed great dysregulations in hepatic metabolic pathways including linoleic acid metabolism, tyrosine metabolism, and methionine metabolism, which are known to be linked with increased body weight gain through hepatic lipid accumulation. The hepatic gene expression involved in lipid transport (e.g., apoa4 and fabp11 ) and lipogenic factors (e.g., ppar ) have been significantly upregulated in the livers of TET exposed zebrafish. Interestingly, the 16 rRNA gene sequence-based zebrafish gut microbial community analysis revealed an enhanced community diversity and altered microbial community composition upon TET exposure. To our knowledge, this is the first study showing that TET exposure can increase the body weight in juvenile zebrafish and the study on the ecotoxicity of antibiotic occurrences in the aquatic system can be further warranted.